Coming together after a tragedy: how the S.S. Eastland disaster of 1915 affected welfare capitalism and helped shape the Hawthorne studies. Issue 2 (7th December 2020) - Zoller, Yaron J.; Muldoon, Jeff
Abstract : Purpose: This paper aims to conduct a historical study using both primary (archival data) and secondary sources to evaluate the social conditions of the community of employees at Hawthorne Works between 1907 and 1933. Design/methodology/approach: This paper evaluates the historical and social context of the 1915 Eastland disaster, specifically, the effects of the Eastland disaster on the community and the company to improve understanding of the contextual background and conditions which influenced the Hawthorne studies. This will also serve as a case study of crisis management. Findings: The findings of the paper argue that the Eastland disaster likely contributed to the expansion of welfare capitalism practices by Western Electric in the 1920s–1930s and established the social and communal conditions which made the Hawthorne studies (1924–1933) possible. Originality/value: Rather than evaluating the Hawthorne studies themselves, this paper focuses on social factors which made the Hawthorne Works plant site and the community serving it an ideal locale to host the famous studies as part of Western Electric's practice of welfare capitalism and a distraction from the traumatic event which scarred the community and urged the Western Electric company to react. This study also provides an early example of crisis management.